Adult Learning and la Recherche Féminine Reading Resilience and Hélène Cixous - Hoult, E.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2012)
Using Hélène Cixous' notion of 'l'écriture féminine' as an analogy for transformational learning and an investigative tool, Hoult explores why some adult learners are able to survive and thrive in the education system, despite facing significantly more challenges than the average student.
Keywords: Philosophy and social sciences; Education; Philosophy of Education; Education, general